The contribution of internal audit in achieving integrity and reliability of accounting information: Case study in President office, Public Service Management - Chale, Joyce (Mzumbe University, 2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the degree of Master of Science in Accounting and Finance (MSc-A&F) of Mzumbe University.